Vaccine hesitancy ‘outbreaks’: using epidemiological modeling of the spread of ideas to understand the effects of vaccine related events on vaccine hesitancy - Alison B. Wiyeh; Sara Cooper; Chukwudi A. Nnaji; Charles S. Wiysonge (Expert Review of Vaccines, 2018)
Introduction: Vaccine hesitancy, a growing global problem which is aggravated by vaccine related rumors and (mis)information, has the potential to reverse the gains from vaccination. Areas covered: We describe a selection of vaccine-related events that have made headlines and highlight the effects that these have had on vaccine acceptance. Drawing on these cases, and an adaptation of an epidemiological modeling of the spread of ideas, we propose that vaccine hesitancy can be grouped into two categories: ‘baseline’ and ‘reactive’ vaccine hesitancy. ‘Baseline’ vaccine hesitancy refers to the level of refusal or delay in acceptance of vaccinations that is constantly present in the population. Though it may vary, changes are unlikely to be sudden or dramatic. ‘Reactive’ hesitancy, which often occurs because of vaccine-related events, is characterized by a rapid spike in levels of hesitancy, usually subsiding at a slow rate. Expert commentary: Different kinds of interventions are needed to address different forms of vaccine hesitancy. Modeling the diffusion of (mis)information during vaccine hesitancy ‘outbreaks’ is essential for designing interventions that will ensure appropriate management of ‘reactive’ hesitancy, and control of ‘baseline’ levels of vaccine hesitancy. More empirical research is needed to test and better understand this hypothesis.